2015
DOI: 10.1016/j.atmosenv.2015.03.039
|View full text |Cite
|
Sign up to set email alerts
|

Non-culturable bioaerosols in indoor settings: Impact on health and molecular approaches for detection

Abstract: h i g h l i g h t sNon-culturable fraction of bioaerosols is important but still misunderstood. Airborne non-culturable agents can be hazardous for human respiratory health. Molecular tools allow the detection of airborne non-culturable microorganisms. Culture-dependent and independent tools should be used for bioaerosol studies. Several research needs relating to non-culturable agents must be addressed. a b s t r a c tDespite their significant impact on respiratory health, bioaerosols in indoor settings remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 145 publications
(128 reference statements)
2
44
0
Order By: Relevance
“…The 2001 National Human Activity Pattern Survey estimated that people in developed countries spend nearly 90% of their time indoors and that time spent indoors has remained fairly uniform over the past few decades2. Humans share indoor spaces with diverse populations of microorganisms from all three domains that create bioaerosols3 and colonize indoor surfaces. Fungal contamination of indoor ecosystems has always been of interest in connection to building structure biodeterioration and serious effects on human health4.…”
mentioning
confidence: 99%
“…The 2001 National Human Activity Pattern Survey estimated that people in developed countries spend nearly 90% of their time indoors and that time spent indoors has remained fairly uniform over the past few decades2. Humans share indoor spaces with diverse populations of microorganisms from all three domains that create bioaerosols3 and colonize indoor surfaces. Fungal contamination of indoor ecosystems has always been of interest in connection to building structure biodeterioration and serious effects on human health4.…”
mentioning
confidence: 99%
“…Bacterial counts greater than 10 5 cells/m 3 were occasionally detected from the recreation area in the basement and the waste storage site outdoors (Table ). Viable bacteria may produce fragments, for example, peptidoglycans and endotoxins, that could cause allergy and inflammation in humans . In addition, high quantities of viable bacteria imply a poor IAQ; indeed, a ceiling limit of 1500 CFU/m 3 has been set for bacterial aerosols as the mandatory IAQ standard of Taiwan .…”
Section: Resultsmentioning
confidence: 99%
“…The optimized PMA‐qPCR method was then applied to air samples collected from various environments to determine the airborne S. aureus counts and assess the feasibility of PMA‐qPCR for field samples. The total counts of viable bacterial bioaerosols were also measured by PMA‐qPCR, considering their implications in human health and indoor air quality (IAQ) . The percentage of S. aureus in relation to total viable bacteria was calculated.…”
Section: Introductionmentioning
confidence: 99%
“…53 A lack of bioaerosol studies targeting viruses and archea has also been identified, further limiting our understanding of the impact of airborne microbes on human health. 123 Several of the studies discussed in this review were based in bioaerosol-emitting facilities, such as WWTP and compost facilities, where the exposure to harmful microbes is a cause for concern for occupational safety reasons and for risk to health of the population in the surrounding area. In such cases the task for current research is to establish suitable doseeresponse relationships to enable health-based exposure limits for bioaerosols to be derived.…”
Section: Air Streamlinesmentioning
confidence: 99%